Parenting Patterns in Instilling Islamic Values in Adolescents - Erni; Pairin (Dirasah: Jurnal Pendidikan Islam, 2025)
Parenting patterns in instilling Islamic religious values in teenagers in Panambea Barata Village, Moramo District, South Konawe Regency. The research focus includes (1) the practice of Islamic religious values in teenagers; (2) parenting patterns in instilling Islamic religious values in adolescent children; and (3) supporting and inhibiting factors that influence parents' parenting patterns for adolescent children. This research uses a qualitative approach with descriptive methods. Data collection was carried out through observation, interviews, and documentation. The data collected was then analyzed through data reduction, presentation, and conclusion. The research results show that the practice of Islamic religious values among teenagers is quite good in terms of morals, but is still minimal in the practice of worship. Parental parenting patterns vary, some are authoritative and some are democratic, but in this village, more democratic parenting patterns are implemented. The supporting factors are the parent's educational background and religious environment, while the inhibiting factors are socioeconomic conditions and the negative influence of social media. Overall, parenting patterns need to be improved, especially in carrying out congregational prayers more optimally. Apart from that, the mosque in the village is reactivated so that teenagers in the village pay more attention to practicing Islamic values in-depth and wise use of social media so that children do what they should prioritize doing.